Study of the Qualitative Characteristics of Rapeseed Oil Obtained by Cold Pressing - L Kleymenova , Natalia; N Bolgova, Inessa; V Kopylov, Maxim; Y Zheltoukhova, Ekaterina (KnE Life Sciences, 2021)
Oil from spring rape seeds obtained by cold pressing was selected as the object of this study. Oil samples were obtained under the following technological conditions: the annular gap was 0.7 mm in a grain chamber and the screw rotation speed was 160 rpm at a pressing temperature of 315 K. The oil composition was studied by gas-liquid chromatography on the Chromotech 5000 apparatus. Rapeseed oil characteristics were obtained with chromatograms. An increased content of linoleic acid 20% (ω6) and linolenic acid 12% (ω3) was revealed in the fatty acid composition of the sample. Fatty acids contribute to lipid metabolism regulation. They are of primary importance in the diet. The presence of 58.6% oleic acid (ω9) was identified. The resulting rapeseed oil had healing properties due to the presence of ω3, ω6 and ω9. Vitamin B, vitamin K, traces of vitamin A, and α, β + γ, δ-tocopherols were found. α, β + γ-tocopherols contribute to the oxidation process. According to these results, rapeseed oil can be confidently recommended for introduction into various food recipes. Keywords: rapeseed oil, vitamins, fatty acid composition